2019
DOI: 10.1055/s-0039-1678582
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Disorder

Abstract: The term vascular cognitive disorder (VCD) refers to a heterogeneous group of disorders in which the primary feature is cognitive impairment attributable to cerebrovascular disease (CVD). This includes not only vascular dementia (VaD) but also cognitive impairment of insufficient severity to meet diagnostic criteria for dementia. VCD is recognized as the second most common cause of dementia after Alzheimer's disease (AD), but prevalence rates vary widely according to the diagnostic criteria employed. There hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 117 publications
(117 reference statements)
0
21
0
Order By: Relevance
“…The diagnosis of vascular dementia requires not only sufficient clinical information but also pathological examinations, neuropsychological examinations, and imaging data [21]. However, when ALI patients develop MCI, the low level of cognitive impairment is not insufficient to interfere with the independence of their lives and does not significantly affect daily abilities [22]; therefore, it often goes unnoticed. Once MCI progresses to clinical discovery or significant neuroimaging (MRI or CT) evidence of cerebrovascular disease, the optimal treatment period has been missed [23].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of vascular dementia requires not only sufficient clinical information but also pathological examinations, neuropsychological examinations, and imaging data [21]. However, when ALI patients develop MCI, the low level of cognitive impairment is not insufficient to interfere with the independence of their lives and does not significantly affect daily abilities [22]; therefore, it often goes unnoticed. Once MCI progresses to clinical discovery or significant neuroimaging (MRI or CT) evidence of cerebrovascular disease, the optimal treatment period has been missed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the further research (GO and pathway enrichment analysis) showed that the mechanism of MBHD to treat VD is mainly related to neuronal apoptosis, nitric oxide synthesis and metabolism, platelet activation, NF-κB signaling pathway-mediated inflammation, oxidative stress, angiogenesis, etc. Current studies have shown that the pathogenesis of VD mainly includes (1) hypoperfusion and hypoxia caused by microvascular circulatory disorders, (2) increased blood-brain barrier permeability caused by endothelial dysfunction, (3) inflammation and oxidative stress damage the nutritional interaction between neurovascular unit cells, (4) ROS and inflammation inhibit the survival of neurons (neuron apoptosis), and (5) the destruction and demyelination of myelin tablets caused by the oxidative and proinflammatory environment caused by cerebral ischemia and hypoperfusion and the breakdown of the blood-brain barrier [1,49,50].…”
mentioning
confidence: 99%
“…Other molecules have shown a limited benefit in patients with CI due to CVD (dl-3-n-butylphthalide, gingko biloba extract, cerebrolysin, actogevin). 72,98 The results were obtained in small samples or only in subgroups of individuals and were not replicated at large scale. Therefore, we see no evidence to recommend these drugs in patients with CI due to CVD.…”
Section: Treatment To Improve Cognition In Patients With CI Due To Cvdmentioning
confidence: 95%